State Selectivity and Dynamics in Dissociative Electron Attachment to CF3I Revealed through Velocity Slice Imaging1. (15th September 2014) - Ómarsson, Frímann H.; Mason, Nigel J.; Krishnakumar, E.; Ingólfsson, Oddur
Abstract In light of its substantially more environmentally friendly nature, CF3I is currently being considered as a replacement for the highly potent global‐warming gas CF4, which is used extensively in plasma processing. In this context, we have studied the electron‐driven dissociation of CF3I to form CF3− and I, and we compare this process to the corresponding photolysis channel. By using the velocity slice imaging (VSI) technique we can visualize the complete dynamics of this process and show that electron‐driven dissociation proceeds from the same initial parent state as the corresponding photolysis process. However, in contrast to photolysis, which leads nearly exclusively to the 2P1/2 excited state of iodine, electron‐induced dissociation leads predominantly to the 2P3/2 ground state. We believe that the changed spin state of the negative ion allows an adiabatic dissociation through a conical intersection, whereas this path is efficiently repressed by a required spin flip in the photolysis process.